The fiscal architecture of the EU cohesion policy - Michael Thöne (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
In its current setup, the European Union is often characterised as slow, decision-impeding, inefficient and therefore not really ready for enlargement. The pandemic, the war in Ukraine, the energy crisis and the increasingly uncertain role in the global economy have further increased the high pressure on the EU to undergo modernisation. In this context, structural and Cohesion Policy is of double interest. With 30 per cent of the regular EU budget, it is one of its most important fields of action - one that has historically grown into a complex and opaque maze of objectives and instruments - and is therefore "part of the problem". At the same time, regional policy is traditionally a "part of the solution" whenever the need arises to pave the way for the enlargement and/or deepening of the EU through financial compensation. The paper sheds light on this dual function of Cohesion Policy by examining its fiscal architecture, which forms the underlying framework for convergence and cohesion policies. In several steps, Cohesion Policy is examined in its function as a European financial equalisation system. The history of regional policy is reconstructed as a development in which the equalisation motive always came first, before Cohesion Policy justifications were applied to instrumental or financial expansions of this policy field. The "Mezzogiorno test" shows that the function of financial equalisation - albeit hidden - continues to dominate; alongside the promotional Cohesion Policy, the equalising Cohesion Policy plays de facto a very important role. This is also illustrated quantitatively and with an in-depth look at the little-analysed mechanism that ensures the allocation of EU funds across the Member States and their regions. Not least with regard to this fiscal equalisation formula, known as the Berlin method, the paper formulates several recommendations for the modernisation of structural policy, which are based on the premise that the purpose of Cohesion Policy to act as a financial equalisation is openly recognised and used productively for the further development of this policy area. The character of vertical fiscal equalisation with a horizontal effect and a strong investment focus should be retained, but further developed in accordance with the principle of subsidiarity. In the course of this, the "luxury fiscal equalisation" can also be reduced, which is currently carried out by allocating cohesion funds even to the richest regions of the EU and which costs 27 billion euros per year. A stronger focus on subsidiarity in cohesion policy would also support Member States in implementing modern, place-based policies, which will also make it easier and more efficient to achieve climate change and broader transformation goals.
Keywords: H70; H77; R11; 330; cohesion policy; European structural and investment funds; EU fiscal equalisation